Bioactive 3-Decalinoyltetramic Acids Derivatives From a Marine-Derived Strain of the Fungus Fusarium equiseti D39 - Zhao, Donglin; Han, Xiaobin; Wang, Dan; Liu, Minghong; Gou, Jianyu; Peng, Yulong; Liu, Jing; Li, Yiqiang; Cao, Fei; Zhang, Chengsheng (Frontiers in Microbiology, 2019)
Two novel 3-decalinoyltetramic acid (3DTA) derivatives, namely fusarisetins C and D (1 and 2), and four known derivatives (3–6) were isolated from the marine-derived fungus Fusarium equiseti D39. Their structures were determined by spectroscopic data, vibrational circular dichroism (VCD) calculations, and X-ray crystallography. Compound 2 was identified as the first fusarisetin to possess an unprecedented carbon skeleton with a tetracyclic ring system comprised of a decalin moiety (6/6) and a tetramic acid moiety. A plausible biosynthetic pathway for the isolated compounds was proposed. All 3DTAs derivatives exhibited a potent phytotoxicity, and 5 also displayed a remarkable anti-phytopathogenic activity superior to the positive control resulting in damage of the cell membrane of P. syringae and ensuing leakage of the intracellular components. Here the phytotoxicity of fusarisetins has been reported for the first time. The OSMAC fermentation optimization approach to give 5 was performed by varying the culture media and salinities. The results showed that potato liquid medium with 1% salinity is the most favorable condition for the production of 5